Are Ada, Katherine, Sally, and Sophie on-Shelf?: Holdings of Award-Winning Juvenile STEM Works in ARL Libraries with a Special Focus on Female-Themed Titles. Issue 3 (12th February 2021) - Pritt, Andrea L.; Lear, Bernadette A.
Abstract: PreK-12 science, technology, engineering, and mathematics (STEM) books are vital resources for student teachers in college-level Education programs. This study takes a best-case scenario approach by exploring the holdings of recent Outstanding Science Trade Books (Books identified by the National Science Teaching Association annually for K-12 students.) at twenty academic libraries. Even among large-budget, research-oriented university libraries chosen for our study, there is considerable variability in the number and types of titles owned. The works most likely to be present in Association of Research Libraries (ARL) libraries include those that have won multiple awards. Titles about female scientists were among the most frequently held and were just as popular as works about males in STEM.